Influence of the level of speed-strength preparedness on the agility of volleyball players 12-13 years old - Oleg Shevchenko; Volodymyr Paievskyi; Yurii Horchanyuk (Kharkiv State Academy of Physical Culture, 2018)
Purpose: determine the impact level of indicators of speed-strength preparedness for the agility of young volleyball players 12-13 years. Material & Methods: analysis of scientific and methodological literature, pedagogical testing of speed-strength qualities and agility, pedagogical experiment, methods of mathematical statistics. The study involved 25 volleyball players aged 12-13 years, training in the basic training group of the second year of training of the sports club "Lokomotiv" in Kharkov. Young athletes were divided into an experimental - 13 people and a control -12 volleyball team. Results: after the introduction of the experimental methodology, a link was found between the level of speed-strength abilities and the agility of volleyball players. Conclusion: the positive influence of development of speed-strength qualities on indicators of agility of volleyball players that is necessary for selection of means and methods in training process of young athletes is proved.